Study on Making Jelly Candy from the Melon Rind - Ragil Ulfa Mariana; Farid Jabbar Al Alif; Rita Dewi Kristiana; Iffah Muflihati; Sari Suhendriani (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
The melon rind is a potential fruit waste to be processed into food products. Jelly candy is one form of processed food that can be made from melon rind. This study aimed to determine the effect of using melon rind on the physical, chemical, and organoleptic characteristics of jelly candy. This study used a completely randomized design with the treatments of 3 types of melon rind from different varieties: golden aroma melon, local melon, and sweet red melon. The results showed that the water content ranged from 16.06 to 21.89%. Analysis of color indicated that the L, a*, and b* values in the golden aroma melon rind treatment were significantly different from the local melon rind and red sweet melon rind treatments. The pH analysis showed that they were not significantly different. In contrast, descriptive tests show results that are not significantly different. The hedonic test showed that the panelists liked dry jelly candy from a golden aroma and local melon rind.